Percy Jackson And The Lightning Thief - Riordan, Rick (London Puffin Books, 2005)
The Lightning Thief is a 2005 American fantasy-adventure novel based on Greek mythology, the first children's novel by Rick Riordan. The opening installment in the series Percy Jackson & the Olympians, the book was recognized among the year's best for children
Keywords: Children- Fantasy